Harper's history of the war in the Philippines - Wilcox, Marrion 1858-1926. (Quezon City Felta Multi-Media, 2003)
Exact reproduction of the original 1900 edition. Contains hundreds of photographs and illustrations. Includes a listing of American volunteer soldiers involved in the conflict.
PDF file.
Distributed by FELTA Multi-Media.
Keywords: Philippines -- History -- Revolution, 1899-1901.